Analysis of the Effectiveness and Efficiency of the Procurement Process in the Procurement Department at PT. Bakrie Auto Parts - Wulandary, Vivia; Zahra; Rachmah, Siti Mabrur (MultiTech Publisher, 2024)
Every company is inseparable from the procurement of goods or services. With the procurement of goods or services being one of the factors that support the operational activities of a company and to maintain the survival of the company, especially companies engaged in the manufacturing industry. One of them PT Bakrie Auto parts also procure goods run by the procurement department, in the process of procuring goods PT Bakrie Auto parts is utilizing technological advances by conducting electronic procurement which aims to increase the effectiveness and efficiency of procurement. The purpose of this research is to determine the effectiveness and efficiency of the procurement process at PT Bakrie Auto parts. The data collection method in this study is the interview method and direct observation, with the analysis method in the form of quantitative non statistical analysis, namely the method of analyzing data without using statistical analysis. The implementation of the procurement of goods carried out by PT Bakrie Auto parts has been running effectively with an assessment of four indicators, namely: indicators of increasing transparency and accountability, indicators of supporting the monitoring process, indicators of meeting the needs of real team information access, and indicators of achieving goals. In addition, the implementation of procurement carried out by PT Bakrie Auto parts has also been running efficiently based on the results of the assessment of the use of the expenditure budget.